(untitled) (Terr@ Plural, 2020)
It is a consensus to recognize the population’s accessibility difficulties to the available urban services. When referring to rural areas, accessibility becomes even more difficult. This article aims to analyze the accessibility of the residents of the rural district of Cipolândia, located in the municipality of Aquidauana/Mato Grosso do Sul State, to urban services available in the regional urban network. Performing a descriptive, qualitative, and quantitative research, supported by bibliographic and documentary research in addition to field research through direct observation and forms application. As a result, it is noteworthy that the district headquarters, although in the performance of the most basic urban functions, has equipment and services that provide the first contact of its residents with the regional urban network, yet with striking limitations. The city of Aquidauana is the main urban center for access to the urban network, thus having a greater influence on the residents of the Cipolândia district, especially for the satisfaction of more basic goods and services such as shopping and banking services. However, when the search is related to services that require greater specialization, the Regional Capital, Campo Grande, is the one that exerts the greatest influence, attracting most of the displacements. In general, access to the urban network is facilitated towards the city of Aquidauana, due to the good conditions of the MS-345 highway, whereas to access Campo Grande, the road system presents worse traffic conditions.